The effect of cutting interval on yield and nutrient composition of different plant fractions of Moringa oleifera tree - Sultana, Nasrin; Alimon, Abdul Razak; Khan, Shahidul Haque; Sazili, Awis Qurni; Yaakub, Halimatun; Hossain, S. M. Jahangir (WFL Publisher, 2014)
An experiment was carried out to evaluate the effect of cutting interval on biomass yield and chemical composition of different plant fractions of Moringa oleifera. In a completely randomized block design experiment, an established Moringa plot was divided into 12 equal plots and subjectedto three cutting intervals of 4, 6 and 8 weeks, each with four replications. The highest fresh and dry matter (DM) yields (t ha-1 cut-1) of total foliage, leaf and stem were obtained at the 8 weeks cutting interval followed by 6 and 4 weeks cutting interval. Effect of leaf to stem ratio was not significant (P>0.05) among harvesting intervals. The CP content of total foliage, leaf and stem was not different (P>0.05) over the harvesting intervals. The acid detergent fibre (ADF), neutral detergent fibre (NDF) and acid detergent lignin (ADL) of total foliage was significantly (P<0.01) lower in 4 and 6 weeks interval than 8 weeks interval. Ca and P contents of leaf and total foliage were not significantly (P>0.05) different among the treatments. The values of IVDMD and IVOMD ranges were from 772.0 to 802.0 and 761.0 to 798.0 g kg-1 DM, respectively. Both yields and chemical compositions of Moringa foliage and leaf suggest that the optimum cutting interval was 8 weeks in rainy season from mature Moringa tree. These data suggest that the higher CP and lower fibre value in the leaf indicate a good protein source for poultry or other monogastric animals and Moringa foliage could be a potential protein source for ruminant livestock.